Death comes in through the kitchen - Dovalpage, Teresa, 1966- (Soho Crime, 2018)
"Set in Havana during the Black Spring of 2003, a charming but poison-laced culinary mystery that reveals the darker side of the modern Revolution, complete with authentic Cuban recipes. Havana, Cuba, 2003: Matt, a San Diego journalist, arrives in Havana to marry his girlfriend, Yarmila, a 24-year-old Cuban woman whom he first connected with because of her food blog. But Yarmi isn't there to meet him at the airport. When he hitches a ride to her apartment, he finds her lying dead in the bathtub. Love-lorn Matt is immediately embroiled in a Cuban adventure he hadn't bargained for: the police and secret service have him down as their main suspect, and in an effort to clear his name, Matt must embark on his own investigation into what happened to Yarmila. The more Matt learns about his erstwhile fiancee, though, the more he realizes he had no idea who she was at all--but did anyone?"--